Sistem Pendukung Pencarian Produk Laptop Berbasis Ontologi - Yuda, Putu Danny Satria Ananta; Eka Karyawati, Anak Agung Istri Ngurah (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana); Vol 11 No 4 (2023): JELIKU Volume 11 No 4, May 2023, 2023)
laptops are now a basic necessity for people who use laptops. The survey results stated that the use of laptops at home reached 77.48% of Indonesians. The laptop chooses that information on your price, business, specifications, .In addition, prospective buyers must ensure that what they get is relevant..Adoption of sematic web technology can overcome these problems. according to the needs and budgets of prospective consumers. This search system will be created using web sematic technology and the data will be mapped into an ontology form as a knowledge base...The ontology model is built using the methodological method, while the system development uses the prototyping method..Research This is expected to be able to facilitate prospective laptop buyers in selecting laptop products that suit their needs and budget